Actividad antibacteriana de algas marinas de Oaxaca, Pacífico Tropical Mexicano - De Lara-Isassi, G; Alvarez-Hernández, S; Lozano-Ramírez, C (Revista de Biología Tropical, 1996)
A total of 18 algal species were collected (31 samples) in eight localities of Oaxaca state coa